Methodical system of formation of creative abilities of future teachers the basics fine arts education - Ivan Kyrychenko (Vasyl Stefanyk Precarpathian National University, 2017)
The article reveals a system of tasks on drawing, painting and composition aimed atformation future pedagogues and artists creative skills in the early stages of teachingfundamentals of fine arts. Key words: methodical system, formation of creative skills, future teachers and artists.